Analysis of A Shaped Column Tall Structure Under Lateral Loading Using ETABS - Abdul Matin Alam; Reetesh Khare (International Journal of Scientific Research in Civil Engineering, 2022)
Presently a-days, the designers frequently restrict the widths of the segments so that all the more free space is accessible and for the great stylish look of the structure without sections distending out of the dividers and corners. Propels in underlying individuals and strategies to oppose sidelong powers are by and large utilized now days to imagine more steady and safe design.In present work with the ultimate objective to differentiate sustained strong construction utilizing customary segments against structure planned with exceptional formed sections considering seismic burdens on G+12 multi-story building having plan estimation 63.20mx29.50m m is shown and taken apart in Etab variation facilitated assembling frame programming. Proportionate static examination and dynamic response range assessment are performed on the design.
Keywords: Structural Stability; Analysis; Advance Techniques; Software's; Columns; Lateral Forces